The Effect of Modern Dressing Moist Wound Healing Technique on the Wound Healing Process in Diabetic Ulcer Patients - Tati Murni Karokaro; Abdi Lestari Sitepu; Fredy Kalvind Tarigan; Dray Kelvin Pandiangan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The main goal in treating diabetic ulcers is to achieve optimal wound healing. So far, many people assume that wounds can heal quickly due to the drying process. However, in fact, a balanced moist environment in the wound actually supports the growth of new cells. Therefore, a wound care method based on the principle of moisture, or known as moist wound healing, is the main key in modern dressing. Moist wound healing is maintaining a moist wound environment using a moisture-retaining dressing. Objective: The aim is to determine the effect of modern moist wound healing dressing on the wound healing process in diabetic ulcers in the inpatient room 4 in front of Grandmed Hospital Lubuk Pakam. Method: The research design used was a Quasy Experiment using a Pretest posttest One Group Design research design with 37 patients as respondents using the Slovin formula. Results: The average value of diabetic ulcer condition in patients before and after Modern Dressing with Moist Wound Healing technique was obtained, namely 601 with a Standard Deviation of 1,163, with the results of the simple Paired T-Test obtained ? 0.05) obtained P value 004 where P value 0.05, then there is an average difference. This means that there is a difference in wound condition in diabetic ulcer patients before and after modern dressing with moist wound healing technique. Conclusion: The modern dressing technique with the principle of moist wound healing aims to maintain wound moisture in the ulcer healing process. Increased exudate production is a natural part of the inflammatory phase in the wound healing process. Based on the results of the research observation, it shows that before Modern Dressing with Moist Wound Healing Technique was carried out, the Mean value was obtained on the sixth day of treatment of 40.30 with a Standard Deviation of 3.302. Meanwhile, after the Modern Dressing Moist Wound Healing technique was carried out, the Mean value obtained on the sixth day of treatment was 31.90 with a Standard Deviation of 2.601, so it is recommended that nurses use the Modern Dressing Moist Healing technique for the wound healing process when treating wounds.